2019
DOI: 10.1016/j.buildenv.2019.106340
|View full text |Cite
|
Sign up to set email alerts
|

Influence of human body geometry, posture and the surrounding environment on body heat loss based on a validated numerical model

Abstract: For accurate prediction of human thermal comfort in indoor space, a fully validated human body-environment interface model is the key factor. In this study, a numerical model for heat transfer simulation between the human body and the environment was developed. Three parameters, including air speed, air temperature, and total heat transfer coefficient at the body surface, were validated against experiments including a manikin placed in a climatic chamber. Based on the verified model, a set of human body-enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 26 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…Some studies have focused on different experimental cabin environments, using different thermal stress evaluation indicators to describe the degree of human heat stress [18][19][20][21]. Fang et al [22] compared several commonly used outdoor thermal indices through experimental tests and surveys and concluded that there was a high correlation between predicted mean vote (PMV) and other indices, indicating that there was a significant difference between the original thermal stress and thermal comfort.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have focused on different experimental cabin environments, using different thermal stress evaluation indicators to describe the degree of human heat stress [18][19][20][21]. Fang et al [22] compared several commonly used outdoor thermal indices through experimental tests and surveys and concluded that there was a high correlation between predicted mean vote (PMV) and other indices, indicating that there was a significant difference between the original thermal stress and thermal comfort.…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al [34] analyzed the possible reasons for this variation, including differences in body geometry, body posture, and airflow patterns in the investigated room.…”
Section: Natural Convectionmentioning
confidence: 99%
“…The thermistor sensor with an accuracy of AE0.1 C (Betatherm/MTNW, Ireland) provided by the manikin system was placed 130 cm above the ground according to ISO 15831: 2004 and 10 cm in front of the manikin according to the research indicating that the thermal boundary layer of the thermal manikin is within 4 cm. 25,26 Table 3 summarizes the measured air temperature. It can be seen that the air temperature of the incubator was a little higher than the set value, especially for 0 C. Hence, the measured values were used for the following analysis.…”
Section: Experimental Conditions and Facilitiesmentioning
confidence: 99%